Hawker 4.0 - Natali, Feliciana (2019)
If no one wants to continue being hawker, who else? The current median age of hawker is 59 years old, yet the younger generation is reluctant to be hawkers. This situation, if persists, may lead to the disappearance of hawkers in the future. In the light of this problem, Hawker 4.0 - which consists of ‘The Stall’ and ‘i-Hawker’ - is created. Hawker 4.0 aims to be a facility for hawkers to succeed in their businesses, which situation may attract future generations to venture into the hawker scene.The Stall is a renewed hawker stall with refined customer flow and sleek modern design specially catered to the taste of younger generation. Order and payment are automated to reduce queue and help hawkers to focus on their food preparation. i-Hawker is a hawker stalls directory app that integrates digital and physical hawker experience. Customers can explore more hawker stalls and get rewarded for purchasing hawker food, while hawkers can establish business profiles and easily market their business using i-Hawker.